PSXII-11 In vitro fermentative parameters of diets containing increasing inclusions of soybean molasses for sheep - Arruda, Maria Carolina G (J Anim Sci, 2019)
The objective of this study was to evaluate the effects of increasing inclusion of soybean molasses (SM) in sheep diets on in vitro gas production, pH, N-NH3 and VFA. Three ruminally-cannulated adult sheep were used as donors of inoculum. The treatments consisted of diets containing 0, 10, 20 and 30% of SM (DM basis) with forage: concentrate ratio of 20:80. The experimental design was completely randomized with repeated measurements over time (2, 6, 12 and 24 hours). Flasks with a volume of 50 mL were used for incubation. Approximately, 0.2 g of sample, 10 mL of the inoculum and 20 mL of the McDougall buffer solution were added into the flasks. Each time consisted of 6 bottles per treatment and 2 bottles without sample (n = 104). Gas production was measured by a pressure transducer. Concentrations of N-NH3 was determined using micro-Kjeldhal apparatus, and VFA was determined by gas chromatography. The disappearance of DM was evaluated by filtration using nylon bags (50 μm porosity). The data were analyzed using the MIXED procedure of SAS. Orthogonal contrasts were used to determine the linear and quadratic effect of SM inclusion. Total concentration of VFA, pH and gas production per g disappeared (mL/g DM disappeared) had no significant effect (P > 0.05). Gas production per incubated g (mL/g DM incubated), disappearance of DM (%) showed increasing linear effect (P < 0.05), with values of 92.87 to 119.64 and 58.48 to 75.40 for 0 and 30% of SM, respectively. N-NH3 (mg/dL) presented a linear decreasing effect (P < 0.05), ranging from 19.27 to 16.95, for 0 and 30% of SM, respectively. The inclusion up to 30% of SM (DM basis) in sheep diets did not affect in vitro fermentation parameters and did not promote a difference in gas production per g disappeared when compared to other treatments.